A randomised controlled trial to evaluate the impact of sexual health clinic based automated text message reminders on testing of HIV and other sexually transmitted infections in men who have sex with men in China: protocol for the T2T Study. Issue 7 (10th July 2017) - Zou, Huachun; Meng, Xiaojun; Grulich, Andrew; Huang, Shujie; Jia, Tianjian; Zhang, Xuan; Luo, Zhenzhou; Ding, Yi; Yang, Ligang; Han, Jinmei; Chen, Weiying; Zheng, Heping; et al.
Abstract : Introduction: The frequency of screening for HIV and other sexually transmitted infections (STIs) among men who have sex with men (MSM) is still low in China. Methods and analysis: A sexual health clinic based randomised controlled trial will be conducted in Guangzhou, Wuxi and Shenzhen, China, enrolling 600 MSM. Eligibility will be judged by the pre-programed iPad based questionnaire: (1) age ≥18 years and (2) have had two or more male anal sex partners, or condomless anal sex with a casual male sex partner, or an STI history, in the past 6 months, and (3) provides a valid mobile phone number. Eligible men will be randomly allocated 1:1 to the intervention arm (with monthly text messages reminding them to test for HIV/STIs) or to the control arm (with no reminders). Men in both arms will complete a questionnaire onsite at enrolment and after 12 months, and another questionnaire online at 6 months. Men in both arms will be tested for HIV, syphilis, anal gonorrhoea/chlamydia and penile gonorrhoea/chlamydia at enrolment and at 12 months. The primary outcome is the rate and frequency of HIV testing within the 12 months after enrolment. The secondary outcome is the rate of unprotected anal intercourse. An assessment of the cost effectiveness of this intervention is also planned. Ethics and dissemination: The study has been approved by the ethical review committees of the University of New South Wales, Australia (HC16803), the Guangdong Provincial Centre for Skin Disease and STI Control (GDDHLS-20160926) and the Wuxi Centre for Disease Control and Prevention (WXCDC2016009), China. Study findings will be submitted to academic journals and disseminated to local health authorities. Trial registration number: Chinese Clinical Trial Registry at: http://www.chictr.org.cn/showprojen.aspx?proj=15752 and WHO International Clinical Trials Registry Platform at: http://apps.who.int/trialsearch/Trial2.aspx?TrialID=ChiCTR-IOR-16009304 .